DEVELOPMENT OF LIEPAJA RESIDENTIAL AREA "GREEN GROVE" DURING THE INDEPENDENT REPUBLIC OF LATVIA - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In Latvia, after restoration of independence on May 4, 1990, the economy was restructured. In Liepaja, without analyzing city's historical planning and not finding successful solutions for inhabitants, many factories closed down. Not getting to know with the Detailed Plan of the residential area "Green Grove", professionally developed by architect Irena Rubauska, and lobbying individual interests, specialists of "Group 93" Ltd. produced a new territorial plan for Liepaja. In 2007, Latvian in prison reform was started. The first prison was decided to build in the residential area "Green Grove". The object of research – Liepaja residential district "Green Grove". Research problem – functional and structural changes of "Green Grove" are implemented without performing the analysis of earlier urban development concepts and do not ensure harmonious development of inhabitants’ living environment. The goal of research – analyze the influence of Liepaja Economic Zone and city development strategies on quality of inhabitants’ living conditions in residential areas of "Green Grove". Main methods applied – this study is based on analysis of archive documents, projects, cartographic materials of urban planning, study of published literature and inspection of buildings in nature.